The effect of warm-up on single and intermittent sprint performance - Wallman, K.; Bishop, D.; Morton, A.; Yaicharoen, P. (Journal of Science and Medicine in Sport, 2011)
Purpose: The effect of warm-up (WUP) on subsequent exercise performance has been equivocal. This may be due to the use of WUP intensities that were self-selected or based on a percentage of maximal oxygen uptake, where participants in a cohort were not working at the same metabolic load. Furthermore, the effect of WUP on repeated sprints that simulate those performed in team sports has not been well studied. Therefore the purpose of this study was to investigate the effects of WUP, versus no WUP, on 4 s single-sprint performance and prolonged intermittent-sprint performance (ISP; 80 min) where sprints simulated those performed in team sports. The first sprint of ISP (WUP and no WUP) was also compared to single sprint performance (WUP and no WUP). Methods: Twelve male, athletes performed four trials on a cycle ergometer consisting of either prolonged ISP or single sprint performance, following either a WUP or no WUP. WUP intensity was performed midway between the lactate and anaerobic thresholds. Results: There were no significant interaction effects between trials for prolonged ISP for total work (J·kg-1), work decrement and power decrement (P = 0.59, P = 0.50, and P = 0.37, respectively). Work for the first sprint of ISP (no WUP) was significantly less (P < 0.001) compared to the first sprint of ISP (WUP) and to both single sprint performance trials (WUP and no WUP). Peak power output (W·kg-1) for single sprint performance (WUP) was significantly higher (P < 0.05) compared to the no WUP trial, and to the first sprint of both ISP trials (WUP and no WUP). Conclusion: WUP improved single sprint performance and the first sprint of prolonged ISP. Use of a pacing strategy during prolonged ISP may explain improved single sprint performance compared to the first sprint of prolonged ISP, as well as similar prolonged ISP between the WUP and no WUP trials.